The application of computational fluid dynamics simulation technique to ocean boat anti-disturbance tracking controller. (8th May 2019) - Yu, Zhenning; Wong, Seng Fat
This article presents the verification problem of estimating boat hull damping parameters using the computational fluid dynamics technique. In addition, a Lyapunov-based path control system will be introduced to centify the estimation result. The controller should satisfy the following features: firstly, maintaining that the boat dynamic model which includes path, velocity, and orientation errors are asymptotically stable; secondly, ensuring the actuation is operating normally under the nonlinear hydrodynamic system and actual environment limitation; thirdly, working with the anti-disturbance algorithm which includes a projection update law. The final part of the article introduces the procedure proving that the computational fluid dynamics simulation result and Lyapunov direct method controller are acceptable for the ocean boat nonlinear dynamic system. It is confirmed that the control system simulation can improve computational fluid dynamics technology instead of an actual experiment. It can solve the estimation problem caused by limitations in equipment or funds.